2017
DOI: 10.1038/ajg.2017.201
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Postoperative Complications Among Inflammatory Bowel Disease Patients Treated Preoperatively With Vedolizumab

Abstract: In the present study, preoperative vedolizumab exposure did not affect the risk of 30-day postoperative complications in UC and CD. Further, larger studies are required to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 41 publications
3
91
0
Order By: Relevance
“…Considering VDZ's gut selectivity, the safety profile has been shown to be favourable . One study using single‐centre data showed that VDZ exposure was not associated with post‐operative complications, including a recent meta‐analysis . However, since VDZ's mechanism of action blocks leucocyte migration into the intestinal lining, wound and anastomotic healing after IBD‐related surgery remains a potential concern .…”
Section: Introductionmentioning
confidence: 99%
“…Considering VDZ's gut selectivity, the safety profile has been shown to be favourable . One study using single‐centre data showed that VDZ exposure was not associated with post‐operative complications, including a recent meta‐analysis . However, since VDZ's mechanism of action blocks leucocyte migration into the intestinal lining, wound and anastomotic healing after IBD‐related surgery remains a potential concern .…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study by Yamada et al . and a pediatric study from the Mayo Clinic, however, did not show an increased risk of infection with preoperative vedolizumab exposure …”
Section: Vedolizumabmentioning
confidence: 81%
“…However, in contrast, Colombel et al found no significant excess risk of serious infections or overall complication rates for IBD patients treated with vedolizumab compared with placebo in the GEMINI trials [882]. Similarly, use of propensity score matching to analyse cohort data did not demonstrate any excess risk of infectious complications with vedoluzimab [879]. There are minimal data on infectious risk with ustekinumab.…”
Section: Crohn's Diseaseinfluence Of Corticosteroids On the Risk Of Pmentioning
confidence: 95%
“…In contrast, several other studies failed to demonstrate an association between overall postoperative infections or anastomotic leakage rate and up to a 12-week interval between surgery and the preceding infliximab administration [293,866,[871][872][873][874][875][876]. A more recent systematic review and meta-analysis and the most recent nationwide prospective cohort study conclude that preoperative use of infliximab does increase the risk of early postoperative complications overall, particularly for infection, in patients undergoing surgery for Crohn's disease [877,878], but even these data are contradicted by another contemporaneous meta-analysis showing no effect [874] and a recent large retrospective cohort study [879].…”
Section: Crohn's Diseaseinfluence Of Corticosteroids On the Risk Of Pmentioning
confidence: 99%